ADAPTASI PSIKOLOGI KLIEN DENGAN KANKER PAYUDARA DI RS NURUL HASANAH KUTACANE TAHUN 2021 - Nurjannah Nurjannah; Nurhasanah Sym (Jurnal Maternitas Kebidanan, 2021)
Breast cancer is a disease that can be experienced by women all over the world and affects every aspect of human life, especially psychosocial aspects. The main psychosocial problems experienced by breast cancer clients are ineffective coping, body image and impaired sexual function. This descriptive study aims to identify psychosocial adaptations of breast cancer clients at Nurul Hasanah Kutacane Hospital. The study was conducted from January 12 to June 4, 2021. Determination of the number of samples using total sampling with the number of samples of 25 people. The research instrument used a self-created questionnaire by researchers consisting of demographic data and psychosocial adaptations of breast cancer clients. The questionnaire has been tested for reliability using KR 20 with a result of 0.7029. The results showed that most of the 24 respondents (96%) had adaptive psychosocial adaptations. This research has implications for educational institutions, nursing practices.